Knowledge, Attitude and Practice of Male Professional and Semi-Professional Footballers Towards Concussion: A look at two countries from the Caribbean Football Union - Sharmella Roopchand Martin; Barrington Gayle; Vanessa Wickham; Lori Ann Miller; Saundria Codling (Caribbean Medical Journal)
Objectives: This study sought to determine the knowledge, attitudes, and practices of male professional or semi-professional footballers towards concussion from two member countries of the Caribbean Football Union.